Meta-Analisis Implementasi Landasan Ilmu Pendidikan Dalam Pengembangan LKS Berbasis Pendekatan Keterampilan Proses Sains Pada Pembelajaran Fisika - Widestra, Rahmi Agustia; Putri, Yulia Herlina (Universitas Negeri Padang, 2019)
This study aims to analyze the implementation of educational science foundation in the development of Worksheets based on the approach of science process skills in Physics learning. This research method is a meta-analysis with a sample of 10 articles in national and international journals. The results of this meta-analysis study are 9 articles having a percentage of 60% and 1 article having a percentage of 40% in implementing the educational foundation. The use of educational foundations analyzed in the article are religious foundations, philosophical foundations, psychological foundations, cultural foundations and social foundations